Avaliação do nível de atividade física, percepção da qualidade de vida e estresse em funcionários de uma escola pública em Miracema do Tocantins - Mercêdes, Poliana Rodrigues (Universidade Federal do Tocantins, 2021)
This study aimed to assess the level of physical activity and the perception of quality of life and stress in employees of a public school in Miracema TO. The growing evolution of technologies causes countless contributions to the social, cultural and biological growth of the human being. The impact of this process of changes is reflected in the educational systems affecting the employees of this group, especially the teaching staff, professionals who are exposed to factors such as long working hours, low wages, malfunctioning of educational policies and degrading working conditions. The stressful processes present in the daily routine of these professionals, who make up the school staff, can lead to a disorder between work and health, causing acute stress situations and, consequently, falling ill. Stress is one of the factors responsible for the population's illness, since it affects all sectors and classes having a direct influence on the quality of life. The present research was characterized as cross-sectional, quantitative in nature, with a descriptive methodological objective. For assessment, the following instruments were used: International Physical Activity Questionnaire (IPAQ) (short version) used to assess the level of physical activity; WHOQOL-Bref was used to assess the Perception of Quality of Life and the Perceived Stress Scale (EPS-10) used to assess the perception of stress in each individual. Results: 27 adults participated in this study, 77.78% of whom were female. Regarding the level of physical activity, 77.78% were classified as active and very active. The perception of general quality of life had an average of 59.01 and the domain that had the highest score was psychological. Perceived stress averaged 17 as a result. Conclusion: The perception of median stress is related to low quality of life in the environment. This indicates a need for intervention in the stressors of the school environment, as well as developing projects aimed at promoting health in order to reduce the number of insufficiently active and sedentary subjects.